CITY RESIDENTS' EXPECTATION FOR PERSUASIVE DAKWAH (A Study in Cimahi City) - Bambang Saiful Ma'arif; umar yusuf; Suliadi Suliadi; Parihat Parihat; Seviyenti Fikroh (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2021)
This paper is the result of research on 'Mapping the Profile of Persuasive Da’wah Agenda in Cimahi City'. Cimahi is the smallest city in Indonesia with 3 sub-districts, known as a center for